Facebook’s ad hoc groups: a potential source of communicative power of networked citizens (Communication & Society, 2017)
Ad hoc groups (sporadically formed on social network sites for achieving particular common objectives) have been seen as a public space for citizen participation and debate. This study focuses on Facebook’s ad hoc groups in Finland. The aim is to detect the potential of these groups to enhance networked citizens’ communicative power for raising societally important issues to public agenda and initiate changes in society. We suggest a categorization of the groups according to their missions, and present their members’ specific motivations and objectives through an online survey. Despite the general entertainment-orientation and self-referential nature of social media, the results show that ambitions and objectives of ad hoc groups differ notably according to their main mission. Especially clear difference is found between discussion groups and those pursuing societal influence. In addition, media analysis is used to discover how much and for what reasons news media have used the specific groups as news sources. Although not strategically seeking media visibility, the societal influence groups gained larger news coverage, related to their thought-provoking topics, connections to current conditions, group membership size and potential to deal with issues of common concern.